2012
DOI: 10.1089/neu.2012.2381
|View full text |Cite
|
Sign up to set email alerts
|

The Frontal Lobe and Thalamus Have Different Sensitivities to Hypoxia-Hypotension after Traumatic Brain Injury: A Microdialysis Study in Rats

Abstract: After traumatic brain injury (TBI), lesions are anatomically heterogeneous, but the spatial heterogeneity of the post-traumatic brain's vulnerability to hypoxia-hypotension (HH) has been poorly studied. Our objective was to compare the effect of HH after TBI on brain energy metabolism into two regions: the frontal lobe and the thalamus. Twenty-eight Sprague-Dawley rats were randomized into four groups: sham, TBI (brain trauma alone, impact acceleration, 450-g weight drop from 1.8 m), HH (blood depletion to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Less changes in edema, ADC and cerebral metabolism have been described following TBI in the thalamus compared to the cortex (Blanie et al, 2012;Ito et al, 1996;Kita and Marmarou, 1994). Ito et al (1996) using the same model than ours (impactacceleration model in rats) found at 2 h, a 17% decrease in ADC in the thalamus vs. a 44% decrease in ADC in the cortex for rats with TBI and HH.…”
Section: Hippocampus Thalamus and Striatum Vulnerability And Hypoxiasupporting
confidence: 68%
See 3 more Smart Citations
“…Less changes in edema, ADC and cerebral metabolism have been described following TBI in the thalamus compared to the cortex (Blanie et al, 2012;Ito et al, 1996;Kita and Marmarou, 1994). Ito et al (1996) using the same model than ours (impactacceleration model in rats) found at 2 h, a 17% decrease in ADC in the thalamus vs. a 44% decrease in ADC in the cortex for rats with TBI and HH.…”
Section: Hippocampus Thalamus and Striatum Vulnerability And Hypoxiasupporting
confidence: 68%
“…Moreover, posttraumatic insult was less aggressive, as only hypoxia was used. Indeed, the combination of hypoxia and hypotension is necessary to obtain edema formation, raise in ICP or changes in cerebral metabolites in this rat model of TBI with secondary insults (Blanie et al, 2012;Gabrielian et al, 2011;Geeraerts et al, 2006Geeraerts et al, , 2008. Recently, Blanié et al (2012) compared the effect of HH after TBI on brain energy metabolism in the frontal lobe and in the thalamus.…”
Section: Cerebral Cortex Vulnerability and Hypoxiamentioning
confidence: 98%
See 2 more Smart Citations
“…They further observed that the combined effects on brain energy metabolism were not related to modifications in cerebral perfusion pressure (CPP) or CBF. Most recently, the spatial heterogeneity of the posttraumatic brain's vulnerability to hypotension-hypoxemia is described using the 'more-hit' combined model [102]. The combined effect of hypotensive-hypoxemia has been definitively demonstrated; however, the combination of other secondary insults is rarely incorporated into the models of TBI and the associated effects on the injured brain are seldom recognized.…”
Section: Experimental Model Of Tbi Complicated By Multi-insultsmentioning
confidence: 99%